2010
DOI: 10.1002/ajmg.a.33243
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome inactivation does not define the development of premature ovarian failure in fragile X premutation carriers

Abstract: Since only 20% of female fragile X premutation carriers develop premature ovarian failure (POF, i.e., amenorrhea before age of 40 years), and since X chromosome inactivation (XCI) determines the phenotypic severity of full mutation women, we reasoned that the development of POF in fragile X premutation carriers could be due to skewed XCI (XCI ratio >80:20). To determine inactivation ratios and activities of the premutations, inactivation patterns were assessed in peripheral blood samples from 101 fragile X pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…In some cohorts studied, such alleles are associated with the highest risk of FXPOI (Spath et al 2011). Even in cohorts where such alleles are not associated with the very highest risk, the risk of FXPOI remains high (Spath et al 2010). Thus, although 130 repeat alleles are less prevalent than smaller alleles, this allele size might allow us to see pathology in animals with a much shorter reproductive life span than humans.…”
Section: Methodsmentioning
confidence: 99%
“…In some cohorts studied, such alleles are associated with the highest risk of FXPOI (Spath et al 2011). Even in cohorts where such alleles are not associated with the very highest risk, the risk of FXPOI remains high (Spath et al 2010). Thus, although 130 repeat alleles are less prevalent than smaller alleles, this allele size might allow us to see pathology in animals with a much shorter reproductive life span than humans.…”
Section: Methodsmentioning
confidence: 99%
“…22,23 Differences in the incidence rates of expanded CGG repeats between fertile and infertile women were assessed using χ 2 analysis. To account for the potential effects of confounding factors, such as age, and the concentrations of FSH, AMH, and inhibin B, multiple regression analysis was performed with the data collected among the infertile women with still ongoing menstrual cycles and confirmed using Spearman rank analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Second, skewed XCI may play a role in modifying the risk or severity of FXPOI, as FMR1 is located on the X chromosome. However, no study has found evidence for skewed XCI based on samples from fresh blood among PM carriers with FXPOI [5,7,28-31]. Assuming that XCI in blood can be used as a proxy for the correct target tissue, one possible explanation for this observation is that the toxic effect of the PM acts during a stage in development when both X chromosomes are active.…”
Section: Reviewmentioning
confidence: 99%